The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1063/1.2959099
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of rectification effects in diffuser/nozzle structures with viscoelastic fluids

Abstract: This paper reports the improvement of rectification effects in diffuser/nozzle structures with viscoelastic fluids. Since rectification in a diffuser/nozzle structure with Newtonian fluids is caused by inertial effects, micropumps based on this concept require a relatively high Reynolds numbers and high pumping frequencies. In applications with relatively low Reynolds numbers, anisotropic behavior can be achieved with viscoelastic effects. In our investigations, a solution of dilute polyethylene oxide was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…Moreover, the elastic instability was found to depend on the rheological parameters of the polymer solution. Dilute polymer solutions were also investigated in various extensional microfluidic devices with cross-slot and expansioncontraction geometries [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the elastic instability was found to depend on the rheological parameters of the polymer solution. Dilute polymer solutions were also investigated in various extensional microfluidic devices with cross-slot and expansioncontraction geometries [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…9 When dealing with PEO dilute solutions, however, the fluid can recirculate within the device inlet giving rise to vortex formation. 29 Nevertheless, due to the relatively small designed angle at the inlet a ¼ 20 , and in the range of Deborah number investigated, we can safely assume that no recirculation phenomena are present. In addition, we did not observe an anomalous particle distribution at the channel entrance.…”
Section: Fig 1 (A)mentioning
confidence: 99%
“…Nguyen and Huang (2001) used this concept to design and fabricate a micropump based on printed circuit board (PCB) technology. Recently, Groisman and Quake (2004) and Nguyen et al (2008) reported that the rectification effect is even stronger if a viscoelastic fluid is employed instead of a Newtonian fluid. To the best knowledge of the authors, none of the previous works investigated multiphase flow in a serial diffuser/nozzle structure.…”
Section: Introductionmentioning
confidence: 99%